IMPLEMENTATION OF CHARACTER EDUCATION THROUGH A PAKEM APPROACH MODEL IN CIVIC EDUCATION - Ponidi, Ponidi (STMIK Pringsewu, 2021)
Research with the implementation of character education through the PAKEM approach model in civic education subjects aims to provide the inculcation of character values that are embedded in humans through learning civic education in Schools. This study uses a qualitative method so that the resulting research procedure is descriptive data from the results of these observations with words, pictures, and not numbers so that the research report contains quotations of data to provide an overview of its presentation. The results of this research are that civic education can be used as a determinant in improving character education by building citizenship education with a new paradigm and developing learning to apply the PAKEM approach. Through character-based civics learning with the application of the PAKEM approach, several conventional Civics learning problems can shift into innovative learning. The use of learning models in every teaching and learning activity is based on character education so that students are always happy and have a meaningful learning concept.